On the feasibility of commercial, legal P2P content distribution. - Rodriguez, Pablo (Computer communication review.)
A spirited panel was recently held at the 10th International Web Caching and Content Distribution workshop on the future of P2P in content distribution [1]. After more than ten years of content distribution research and technology efforts, P2P is emerging as an alternative solution to solve the mass distribution of large digital content. However, using P2P for commercial content distribution faces a number of serious challenges. Issues such as content protection, impact on ISPs, security, end-to-end connectivity, and business models need careful consideration before P2P an be used as an efficient tool by content providers. In this paper, we summarize the issues brought up in discussion, and delve deeper into the feasibility of commercial, legal P2P content distribution solutions